Improving the Reading Ability of Student with Mild Intellectual Disability through Sight Word Intervention: A Single Case - Zakiah Ulya; Cici Oktaviani; Beny Al Fajar; Asfi Yanti WE (Pedagogik Journal of Islamic Elementary School, 2025)
Reading ability is crucial for academic success, yet students with mild intellectual disabilities often struggle with early reading components. This single-case study aimed to evaluate the effectiveness of a sight word intervention on the reading ability of an 11-year-old female student with Mild Intellectual Disability (MID). Employing a single-case experimental design, the intervention utilized structured direct instruction with a constant time delay technique and high-frequency flashcards for 2- and 3-syllable words across baseline, intervention, and post-intervention phases. Visual analysis of the data revealed significant improvements in the participant's ability to read both 2-syllable and 3-syllable words, characterized by substantial level increases, positive and consistent trends, low variability, and minimal overlap between phases. Notably, reading gains were retained post-intervention. These findings suggest that structured sight word intervention, focusing on repeated practice and word recognition automation, is an effective strategy for enhancing foundational reading skills in students with MID, offering valuable implications for inclusive education.